Prototype of Automatic Cafe Management System (ACMS) Based on Internet of Things (IOT) - Sabariman Sabariman; Erris Fernandy (Universitas Internasional Batam, 2022)
The COVID-19 Pandemic changes people’s lifestyle nowadays. Physical interactions between person have lessened due to laws passed by central governments concerning its limitations. It’s no surprise this impacted businesses that needs face-to-face meetings, such as cafés or restaurants. Based on such facts, prototype for Automatic Café Management System (ACMS) based on Internet of Things (IOT) is designed. ACMS allows customers to order food through web-based system that can be accessed with their gadgets. The system is equipped with a line follower robot to act as waiter/waitress. With such system, physical contacts in café or restaurant settings can be reduced significantly.